HMGB1-Induced Hepatocyte Pyroptosis Expanding Inflammatory Responses Contributes to the Pathogenesis of Acute-on-Chronic Liver Failure (ACLF) - Hou W; Wei X; Liang J; Fang P; Ma C; Zhang Q; Gao Y (Dove Medical Press, 2021)
Weixin Hou,1- 4 Xiaoyi Wei,1,2 Jiajun Liang,1- 4 Peng Fang,5 Chongyang Ma,1,2 Qiuyun Zhang,1,2,* Yanbin Gao3,4,* 1Department of Hepatology, School of Traditional Chinese Medicine, Capital Medical University, Beijing, People's Republic of China; 2Department of Hepatology, Beijing Key Laboratory of Traditional Chinese Medicine Collateral Disease Theory Research, Capital Medical University, Beijing, People's Republic of China; 3Department of Endocrinology, School of Traditional Chinese Medicine, Capital Medical University, Beijing, People's Republic of China; 4Department of Endocrinology, Beijing Key Laboratory of Traditional Chinese Medicine Collateral Disease Theory Research, Capital Medical University, Beijing, People's Republic of China; 5Department of Infectious Diseases, First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiuyun Zhang; Yanbin GaoSchool of Traditional Chinese Medicine, Capital Medical University, No. 10 You An Men Wai, Xi Tou Tiao, Feng Tai District, Beijing, 100069, People's Republic of ChinaTel +86 10 8391 1638; +86 10 8391 1720Email 19970059@ccmu.edu.cn; gyb@ccmu.edu.cnBackground: Acute-on-chronic liver failure (ACLF) is a critical disease with a high fatality rate. Immune dysfunction and inflammatory responses are key risk factors in ACLF. Pyroptosis is a form of programmed cell death characterized by the release of inflammatory cytokines, which causes the strong inflammatory responses. High mobility group box-1 (HMGB1) could induce pyroptosis and is closely related to ACLF. However, the role of HMGB1-induced hepatocyte pyroptosis in ACLF has never been proposed; whether HMGB1-induced hepatocyte pyroptosis participates in the development of ACLF and the mechanisms involved are barely understood.Purpose: This study aimed to clarify the roles of HMGB1-induced hepatocyte pyroptosis in ACLF and the molecular mechanisms involved.Methods: Wistar rats were randomly divided into five groups, viz.: Normal, ACLF model, HMGB1 inhibitor, Caspase-1 inhibitor, and HMGB1 inhibitor+Caspase-1 inhibitor groups. The ACLF rat model was established using 40% carbon tetrachloride-induced liver fibrosis, followed by D-galactosamine and lipopolysaccharide joint acute attacks. The liver function, coagulation function and pathological damage of rats in each group were evaluated. The biological mechanisms of HMGB1-induced pyroptosis and the release of inflammatory cytokines were investigated using Western blot, quantitative real-time PCR (RT-qPCR), immunofluorescence, enzyme-linked immunosorbent assay (ELISA), and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay.Results: The liver function and coagulation function of ACLF rats were seriously impaired; liver tissue showed massive or submassive necrosis, accompanied by inflammatory cell infiltration; the percentage of pyroptotic hepatocytes significantly increased, and a large number of inflammatory cytokines were released. The expression levels of pyroptosis-related genes and proteins in liver tissues and serum significantly increased. But these phenomenons were improved by the inhibition of HMGB1, and the dual inhibition of HMGB1 and Caspase-1 showed a stronger effect.Conclusion: The findings indicate, for the first time, that pyroptosis is a crucial pathophysiological event of ACLF involved in its pathogenesis, and HMGB1-induced hepatocyte pyroptosis expands inflammatory responses to aggravate ACLF, suggesting that it may be a potential therapeutic target for ACLF treatment.Keywords: HMGB1, pyroptosis, inflammatory response, molecular mechanism of ACLF, ACLF treatment